Assessment of Mealybug (Hemiptera: Pseudococcidae) Species Diversity in Different Host Plants from Selected Locations in Sri Lanka Using Morphological and Molecular Methods - Gajapathy, K.; Sathsarani, K.W.I.; Terensan, S. (Ceylon Journal of Science, 2026)
Mealybugs are economically significant, sap-sucking insects causing substantial damage to crops. Although some studies exist, few have combined classical morphological and molecular approaches with an assessment of their economic significance. This study aimed to identify mealybug species based on morphology, analyze their host preference, and confirm the identification using DNA markers. Mealybug samples were collected from randomly selected fields from Kilinochchi, Jaffna, and Monaragala districts in Sri Lanka. Morphological identification was done using taxonomic keys. PCR amplification was performed for the D3 region of the 28S rDNA. A phylogenetic tree was constructed using the Maximum-Likelihood method with the Kimura 2-parameter model and the Gamma distribution. Ten mealybug species, representing seven genera, were identified from different districts and host plants, including Phenacoccus solenopsis, Ferrisia virgata, Coccidohystrix insolita, Planococcus minor, Phenacoccus solani, Planococcus lilacinus, Phenacoccus manihoti, Paracoccus marginatus, Pseudococcus viburni, and Rastrococcus mangiferae. Notably, P. solenopsis, F. virgata, P. minor, P. lilacinus, and P. marginatus were found to infest multiple host plant species, indicating their broader host preference. P. solani and P. manihoti are reported for the first time from Sri Lanka. Molecular data validated the morphological identification, and phylogenetic analysis revealed distinct clades representing separate genera exhibiting monophyletic and paraphyletic relationships among them. Field observations indicated a frequent association between mealybugs and ants, where Oecophylla smaragdina and Technomyrmex albipes were observed on P. lilacinus-infested guava trees. Furthermore, natural enemies of mealybugs, such as mealybug destroyers, were observed in 20% (n=6) of the fields. This comprehensive study provides valuable insights into mealybug species diversity, host preference, and insect associations, which are critical for developing effective integrated pest management strategies tailored for specific regions and host plants.
Keywords: Insect pest; Host preference; Insect associations; DNA markers; Phylogenetic analysis